PENGEMBANGAN SISTEM PENDUKUNG KEPUTUSAN PENGADAAN DAN PERSEDIAAN BARANG DENGAN METODE PERPETUAL INVENTORY METHOD DAN ECONOMIC ORDER QUANTITY ( Studi Kasus : Divisi Logistik Rumah Sakit Krakatau Medika Cilegon) - Gilang Sonar Amanu; Yuliani Indrianingsih (Institut Teknologi Dirgantara Adisutjipto, 2015)
The accuracy of data is the capital for making a very useful information for the company business continuity. The value of data can be very expensive if it can be made into a good information and the right target. Procurement and inventory data is one of the things to note in particular the logistics division on the company. Therefore it needs a system using a particular method that can be support the data management of goods procurement and it can also help the managers take the decision of stock control. Based on that, it can be developed to integrated system between procurement data processing and the amount of purchasing materials a single web-based application that implement a method of stock record such as perpetual inventory method and economic order quantity method as well as the methods used to support the decision in calculating the amount of inventory to be optimal. Using the development of the decision support system, some errors related to the recording of data on procurement and inaccuracies in determining the amount of inventory can be reduced. Then the company can avoid the material losses.